Isolation of Female Germline Stem Cells from Mouse and Human Ovaries by Differential Adhesion - Maryam Saber; Pouya Tavakol; Fereshteh Esfandiari (International Journal of Cell Biology)
Spermatogonial stem cell (SSC) counterparts known as female germline stem cells (fGSCs) were found in the mammalian ovary in 2004. Although the existence of fGSCs in the mammalian postnatal ovary is still under controversy, fGSC discovery encourages investigators to better understand the various aspects of these cells. However, their existence is not accepted by all scientists in the field because isolation of fGSCs by fluorescent activated cell sorting (FACS) has not been reproducible. In this study, we used differential adhesion to isolate and enrich fGSCs from mouse and human ovaries and subsequently cultured them in vitro. fGSCs were able to proliferate in vitro and expressed germ cell-specific markers Vasa, Dazl, Blimp1, Fragilis, Stella, and Oct4, at the protein level. Moreover, mouse and human fGSCs were, respectively, cultured for more than four months and one month in culture. Both mouse and human fGSCs maintained the expression of germ cell-specific markers over these times. In vitro cultured fGSCs spontaneously produced oocyte-like cells (OLCs) which expressed oocyte-relevant markers. Our results demonstrated that differential adhesion allows reproducible isolation of fGSCs that are able to proliferate in vitro over time. This source of fGSCs can serve as a suitable material for studying mechanisms underlying female germ cell development and function.